2015
DOI: 10.1186/s13287-015-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of xeno-free expansion and transplantation of autologous ocular surface epithelial stem cells via contact lens delivery: a prospective case series

Abstract: IntroductionDepletion of limbal stem cells leads to a debilitating condition known as limbal stem cell deficiency, characterised by impaired corneal wound healing and poor vision. The aim of this study was to determine whether delivering progenitor cells on a contact lens is a viable and effective alternative to current transplantation techniques, which are complicated by biological and xenogeneic materials.MethodsSixteen eyes of 16 patients who had total (n = 14) and partial (n = 2) limbal stem cell deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 51 publications
2
49
0
1
Order By: Relevance
“…Both questionnaires (Appendix I, Appendix II) received input from senior leading ophthalmologists and senior ocular scientists across five states in Australia and New Zealand. Severe LSCD was defined and characterized by; at least 6 clock hours of whorl‐like epitheliopathy, an opaque epithelium arising from the limbus, late fluorescein staining of the involved epithelium, and superficial neovascularization or conjunctivalization . The initial questionnaire (No.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Both questionnaires (Appendix I, Appendix II) received input from senior leading ophthalmologists and senior ocular scientists across five states in Australia and New Zealand. Severe LSCD was defined and characterized by; at least 6 clock hours of whorl‐like epitheliopathy, an opaque epithelium arising from the limbus, late fluorescein staining of the involved epithelium, and superficial neovascularization or conjunctivalization . The initial questionnaire (No.…”
Section: Methodssupporting
confidence: 91%
“…Severe LSCD was defined and characterized by; at least 6 clock hours of whorl-like epitheliopathy, an opaque epithelium arising from the limbus, late fluorescein staining of the involved epithelium, and superficial neovascularization or conjunctivalization. 7,8,[11][12][13] The initial questionnaire (No. 1) requested patient demographics including; age, sex and postcode, as well as date of diagnosis, how the diagnosis was made, investigations performed, other ocular disease, the underlying diagnosis, CL wear, previous limbal grafts, medical, drug and surgical history, and any treatment initiated after diagnosis.…”
Section: Data Collectionmentioning
confidence: 99%
“…A number of research groups, however, have worked on improving in vitro experiments [11,20] in an effort to ensure that only the most suitable materials progress to human trials. A recent publication by Bobba et al did, however, use contact lens delivery for stem cells to human eyes [21] with generally positive results, citing only two (of sixteen) patients suffering minor complications from contact lens insertion and removal. It is necessary to note that the type of procedures documented for stem cell transplant would be inherently more prone to complications than the type of contact lens use proposed in the majority of works cited in this article.…”
Section: Introductionmentioning
confidence: 93%
“…Recent efforts were focused on developing xenobiotic-free LESC cultures with no feeder cells or with human cells. Human autologous serum has been used to expand LESC on HAM (Shahdadfar et al, 2012) or on soft contact lenses (Bobba et al, 2015). The latter technique has been used in a clinical trial in 16 LSCD patients with reported success in 10 of 16 eyes (63%) at a median follow-up time of 2.5 years with the advantage of autologous transplantation (Bobba et al, 2015).…”
Section: Corneal Epithelial Wound Healingmentioning
confidence: 99%